Análisis comparativo de herramientas digitales y su incidencia en los procesos administrativos de la unidad de gestión de avalúos y catastro en el gad mocache, año 2024. - Terán Soriano , Yuddy Geoconda (2025)
The main purpose of this research, titled Comparative Analysis of Digital Tools and their Impact on the Administrative Processes of the Appraisal and Cadastre Management Unit in the GAD Mocache, 2024, was to evaluate the impact of digital tools versus traditional ones on the efficiency and effectiveness of the administrative processes of this unit. The research, with a mixed approach, applied qualitative and quantitative methods, including surveys and interviews, to analyse the current situation and the effects of digitalisation. Problems were identified such as reliance on manual databases and lack of technological training, which limits operational efficiency and the quality of service to citizens. The results highlighted the need to modernise administrative systems to optimise resources, reduce errors and improve transparency. Recommendations were made to implement digital technologies that contribute to strengthening public management in Mocache.